Effect of physical modification of matrix by nano(polyvinyl alcohol) fibers on fatigue performance of carbon fiber fabric-reinforced vinylester composites. (December 2016) - Shao, Yongzheng; Okubo, Kazuya; Fujii, Toru; Shibata, Ou; Fujita, Yukiko
The vinylester resins were physically modified by 0.05 and 0.1 wt% nano polyvinyl alcohol fibers with about 80 nm in diameter prepared by electrospinning. Addition of nano polyvinyl alcohol fiber with 0.05–0.1 wt% improved the fracture toughness of vinylester resin slightly by ∼14.3%, while the carbon fiber/vinylester resin adhesion was almost unchanged. Then, carbon fiber/vinylester resin composites were fabricated by using modified vinylester resin as matrix and carbon fiber plain-woven fabrics as reinforcement. Low and high-cycle fatigue tests were conducted under the laboratory condition as well as static tensile tests. The tensile strength of carbon fiber/vinylester resin/polyvinyl alcohol composites increased slightly due to increased resistance to damage propagation at transverse bundles and resin-rich region. The fatigue properties of carbon fiber/vinylester resin composites were improved significantly by 3–50 times with the addition of no more than 0.1 wt% nano polyvinyl alcohol fibers. Due to the incorporation of nano filler, damage degree in carbon fiber/vinylester resin/polyvinyl alcohol composite was reduced at the fatigue initial stage based on thermoelastic stress damage analysis. Furthermore, a delay of delamination growth was found as well at the fatigue middle stage according to CT-scan and scanning electron microscopy investigation. The resistance to fatigue damage accumulation due to energy absorption by the addition of nano fiber contributed to fatigue life extension.